Exploration of Children's Creativity through Learning Center Balok at 4–5 Years Old - Asma, Asma; Kusumawardani, Ratih; Asmawati, Luluk (Darul Yasin Al Sys, 2025)
This study explores the implementation of the Beam Center Learning Model (Balok Center Learning) in optimizing the creativity of children aged 4–5 years. Employing a descriptive qualitative research method, data were collected through observation, interviews, documentation, and field notes. The primary objective was to assess the effectiveness of structured learning through beam center activities in enhancing early childhood creativity. The findings reveal that the creativity of children in this age group was significantly optimized, as evidenced by the frequent and observable emergence of creative behaviors across various domains in nearly all participants. This suggests a strong correlation between the learning model and children's creative development. The study concludes that the Beam Center Learning Model is effective in fostering creativity among children aged 4–5 years, as demonstrated in the learning environment at Irma Serang Kindergarten. These results underscore the importance of structured, play-based learning environments in early childhood education to support cognitive and creative growth.